A time series analysis of road traffic fatalities in Malaysia / Yusria Darma - Yusria, Darma (2017)
In Malaysia, with the current road safety developments, it is perceived that the target of the latest Road Safety Plan of Malaysia 2014–2020 that is the main objective is to reduce the deaths in 2020 by 5,358 deaths may not be achieved. Even though various interventions and road safety measures have been implemented through the development of legislations, standards, guidelines and integrated road safety programmes. The primary objectives of this study are: (1) to describe the characteristics of road safety in Malaysia, (2) to investigate the impact of road safety measures in reducing the rate of fatalities, (3) to investigate the factors that influencing the rate of fatalities and (4) to develop time series models to predict the rate of road traffic fatalities in Malaysia. In order to achieve these objectives, three forecasting models are developed based on the time series analysis technique, namely: (1) autoregressive integrated moving average model, (2) transfer function-noise model and (3) state-space model. The multiple regression is used to select the explanatory variables that are correlated significantly with the number of road traffic fatalities. Then, these variables are the input variables for the state-space model. The effectiveness of a road safety measure is checked with the autoregressive integrated moving average and transfer function-noise model. Whilst, for forecasting the fatalities up to year 2020, the autoregressive integrated moving average, transfer function-noise and state-space models are employed. Based on the results, the characteristics of the current road safety in Malaysia are: (1) the major victims of road traffic accidents are motorcyclists, (2) young adult drivers/riders aged 16–25 years make up the highest percentage of the total fatalities, with a value of 35%, and (3) the highest rate of fatal accidents per kilometre occurs at expressways. In addition, the effectiveness of a number of road safety measures is also investigated in this study. The results show that the enactment of the Seat Belt Rules in 1978 decreases the rate of car driver fatalities by 58%. However, the Motorcycle Daytime Running Headlight Regulation in 1992 is not an effective road safety measure to reduce the rate of motorcycle fatalities throughout the nation. In contrast, the Integrated Road Safety Operations (Ops Sikap) is an effective measure. The National Road Safety Plan 2006–2010 decreases the rate of the total road traffic fatalities by only 9%. This achievement is rather low compared to the targeted value of 52.4%. The results show that the significant explanatory variables to forecast the fatalities are: (1) the number of hospital beds per 1,000 people, (2) the percentage of registered motorcycles and (3) road length. Moreover, it is expected that the targeted rate of fatalities of 2.0 per 10,000 registered vehicles will be achieved by year 2023 with intensive enforcement. However, drastic actions need to be taken to achieve the target in the Road Safety Plan 2014–2020.